Pernikahan Tanpa Persetujuan Salah Satu Pihak dalam Perspektif Hukum Perdata dan Hukum Islam - Ahmad Uno; Titin Samsudin; Dedi Sumanto (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2022)
There are several reasons for a husband to marry without asking his partner for approval, disharmony in domestic relations, boredom to his wife, his wife's beauty has decreased, the service for inner needs has decreased because the wife has reached a monoupous period, the wife often utters excessive words that causing confusion a husband or wife has neglected the dress code accompanied by not wearing make up. Things like this can influence a husband to marry a second time. The state guarantees religious life and has participated in securing it through statutory regulations, even many legal products that refer to the material of Islamic law. Law Number 1 of 1974 concerning Marriage which reflects the government's appreciation and concern for the joints in religious teachings, especially Islam. Islamic law has really paid attention to family problems, it is the first foundation in building an ark for marriage in the community.